Attributable Mortality of Candida Bloodstream Infections in the Modern Era: A Propensity Score Analysis . (5th January 2022) - Mazi, Patrick B; Olsen, Margaret A; Stwalley, Dustin; Rauseo, Adriana M; Ayres, Chapelle; Powderly, William G; Spec, Andrej
Abstract: Background: This study quantifies the mortality attributable to Candida bloodstream infections (BSI) in the modern era of echinocandins. Methods: We conducted a retrospective cohort study of adult patients admitted to Barnes Jewish Hospital, a 1368-bed tertiary care academic hospital, in Saint Louis, Missouri, from 1 February 2012 to 30 April 2019. We identified 626 adult patients with Candida BSI that were frequency-matched with 6269 control patients that had similar Candida BSI risk-factors. The 90-day all-cause mortality attributable to Candida BSI was calculated using three methods—propensity score matching, matching by inverse weighting of propensity score, and stratified analysis by quintile. Results: The 90-day crude mortality was 42.4% (269 patients) for Candida BSI cases and 17.1% (1083 patients) for frequency-matched controls. Following propensity score-matching, the attributable risk difference for 90-day mortality was 28.4% with hazard ratio (HR) of 2.12 (95% confidence interval [CI], 1.98–2.25, P < .001). In the stratified analysis, the risk for mortality at 90 days was highest in patients in the lowest risk quintile to develop Candida BSI (hazard ratio [HR] 3.13 (95% CI, 2.33–4.19). Patients in this lowest risk quintile accounted for 81(61%) of the 130 untreated patients with Candida BSI. Sixty-nine percent of untreated patients (57/83) died versus 35% of (49/127) of treated patients ( P < .001). Conclusions: Patients with Candida BSI continue to experience high mortality. Mortality attributable to Candida BSI was more pronounced in patients at lowest risk to develop Candida BSI. A higher proportion of these low-risk patients went untreated, experienced higher mortality, and should be the target of aggressive interventions to ensure timely, effective treatment. Abstract : In the modern era of echinocandins, this study found the crude and attributable mortality of Candida bloodstream infections remain high—42% and 28%, respectively. Patients at the lowest risk of developing infection were found to have the highest attributable mortality.∗